Drug recall: An incubus for pharmaceutical companies and most serious drug recall of history - Nagaich, Upendra; Sadhna, Divya (International Journal of Pharmaceutical Investigation)
There has been an increasing trend in the number of prescribed and over-the-counter drug recall over the last few years. The recall is usually due to company’s discovery, customer’s complaint or Food and Drug Administration (FDA) observation. The process of recall involves a planned specific course of action, which addresses the depth of recall, need for public warning, and the extent of effectiveness checks for the recall. The FDA review and/or recommend changes to the firm’s recall strategy, as appropriate. The critical recall information list includes the identity of the product; summary of the failure; amount of product produced in the distribution chain and direct account. Product recalls clashes thousands of companies every year affecting: sales, testing customer relationships and disrupting supply chains. Drug recall is incubus for pharmaceutical companies. It effects the reputation of the company. The reason for the recall can be divided into two categories: manufacturing affined and safety/efficacy affined. It is essential to follow all the guidelines related to drug development and manufacturing procedure so as to minimize drug recall.
Keywords: Drug product recall; guidelines; process; recall information